(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to analyse the relationship between self-confidence and motivation with the peak performance of football athletes at Persipa Pati Club. The study is grounded in the understanding that psychological aspects play a crucial role in achieving optimal athletic performance, with self-confidence and motivation being two of the most significant internal factors influencing performance outcomes. A descriptive quantitative approach was employed, involving a total of 21 athletes from Persipa Pati Club as research participants. Data were collected using standardised and validated questionnaires, and statistical analysis was conducted using the Spearman Rank correlation test through SPSS software version 29. The results revealed a significant and positive relationship between self-confidence and peak performance (r = 0.671; p = 0.001), as well as between motivation and peak performance (r = 0.674; p = 0.001). These findings indicate that athletes who possess higher levels of self-confidence and motivation are more likely to achieve their peak performance in competitive environments. The strong correlations also highlight the importance of psychological readiness alongside physical and technical preparation in football. As a practical implication, it is recommended that coaches and club management integrate psychological training, such as mental skills development and motivational strategies, into their regular programs. By doing so, athletes can maintain psychological resilience and consistent high-level performance throughout the season. This study contributes to the growing literature on sports psychology in Southeast Asian football settings, particularly within regional clubs.